2017
DOI: 10.1162/jocn_a_01025
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of Attentional Networks and Default Mode Network during the Resting State Reflect Variations in Cognitive States: Evidence from a Novel Resting-state Experience Sampling Method

Abstract: Neuroimaging studies have revealed the recruitment of a range of neural networks during the resting state, which might reflect a variety of cognitive experiences and processes occurring in an individual's mind. In this study, we focused on the default mode network (DMN) and attentional networks and investigated their association with distinct mental states when participants are not performing an explicit task. To investigate the range of possible cognitive experiences more directly, this study proposes a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
80
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 77 publications
9
80
0
2
Order By: Relevance
“…Different cognitive processes also influence both the activation and connectivity of the DMN during resting-state scanning (Bellana, et al, 2017; Benjamin, et al, 2010; Chou, et al, 2017; Demertzi, et al, 2011; Van Calster, et al, 2016; Yan, et al, 2009). Although task-based fMRI has indicated that DMN regions increase in activity for episodic memory and internally driven mentalizing tasks (Buckner, et al, 2008), our findings suggest that relatively long bouts of minimally guided autobiographical retrieval can produce robust changes in the same activity correlation measures used to define networks via resting-state fMRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different cognitive processes also influence both the activation and connectivity of the DMN during resting-state scanning (Bellana, et al, 2017; Benjamin, et al, 2010; Chou, et al, 2017; Demertzi, et al, 2011; Van Calster, et al, 2016; Yan, et al, 2009). Although task-based fMRI has indicated that DMN regions increase in activity for episodic memory and internally driven mentalizing tasks (Buckner, et al, 2008), our findings suggest that relatively long bouts of minimally guided autobiographical retrieval can produce robust changes in the same activity correlation measures used to define networks via resting-state fMRI.…”
Section: Discussionmentioning
confidence: 99%
“…There is high variability in the cognitive states that occur during the resting state, frequently reported to include inner speaking, visual imagery, and sensory awareness (Chou et al, 2017;Hurlburt, Alderson-Day, Fernyhough, & Kuhn, 2015;Van Calster, D'Argembeau, Salmon, Peters, & Majerus, 2016). Autobiographical memory retrieval involves a variety of the same processes which, although not explicitly probed during the resting state, do spontaneously occur (Kucyi, Tambini, Sadaghiani, Keilholz, & Cohen, in press).…”
mentioning
confidence: 99%
“…The mind can start to wander away from the immediate external environment during periods of wakeful rest (akin to task-free, resting-state) as well as during mental activities with externally imposed constraints (akin to experimental task settings). Indeed, the neural underpinnings of MW have been investigated separately in resting-state studies (Doucet et al, 2012;Godwin et al, 2017;Gorgolewski et al, 2014;Poerio et al, 2017;Turnbull et al, 2019;Van Calster, D'Argembeau, Salmon, Peters, & Majerus, 2017; ing the brain dynamics related to MW during rest and task (Christoff et al, 2016;Kucyi, 2017;Zabelina & Andrews-Hanna, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Resting-state fMRI studies have employed several types of retrospective measures to assess spontaneous thoughts: Amsterdam Resting-State Questionnaire (ARSQ)9, New York Cognition Questionnaire (NYC-Q)101112, and Resting-State Questionnaire (ReSQ)1314. Alternatively, mind-wandering has been assessed using experience or thought sampling in conjunction with resting-state fMRI scanning151617181920. While regions within the default mode network are involved in mind-wandering, a number of other brain regions outside the default mode network also show associations with various contents and forms of spontaneous thoughts1015162122.…”
mentioning
confidence: 99%